Single-Cell Immunology and Multi-Omics: Recent Advances and Emerging Applications in Precision Medicine - Nia Ayuni Putri (Jurnal Kesehatan dan Kedokteran, 2026)
The rapid advancement of single-cell sequencing technologies has revolutionized immunological research by enabling comprehensive characterization of immune cells at single-cell resolution. Conventional bulk analytical methods often fail to capture cellular heterogeneity, limiting the understanding of immune mechanisms underlying cancer, autoimmune diseases, infectious disorders, and neurodegenerative conditions. The integration of multi-omics technologies offers new opportunities to overcome these limitations and accelerate precision medicine. Objective: This review aims to synthesize recent advances in single-cell immunology and multi-omics, evaluate their applications across major immunological fields, and identify emerging opportunities and challenges for clinical translation. Methodology: This study employed a qualitative narrative literature review using a structured literature search. Scientific publications were retrieved from PubMed, PubMed Central, Google Scholar, and bioRxiv. Eligible studies were selected based on predefined inclusion criteria and analyzed using thematic narrative synthesis to identify technological developments, translational applications, methodological challenges, and future research directions. Findings: The review demonstrates that single-cell RNA sequencing, CITE-seq, spatial transcriptomics, and integrated multi-omics have substantially improved the identification of immune cell heterogeneity, cellular communication, and disease-specific molecular mechanisms. These technologies have advanced immune atlas construction, enhanced understanding of tumor immune microenvironments, improved characterization of autoimmune diseases, and revealed novel neuroimmune interactions. Artificial intelligence and computational biology further strengthen data integration and biological interpretation. Implications: The findings support the application of single-cell multi-omics in biomarker discovery, disease stratification, therapeutic target identification, and personalized treatment strategies while highlighting the need for standardized analytical pipelines and clinical validation. Originality: This review provides an integrated synthesis of technological innovation, computational methodologies, immune atlas research, oncology, autoimmune diseases, and neuroimmunology within a unified precision immunology framework, offering a comprehensive perspective that extends beyond previous technology- or disease-specific reviews.